Capital market developments in the Bahamas : are we ready for a stock exchange - Demeritte, Kevin ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Looks at the case of the Bahamas as it seeks to follow in the footsteps of other regional economies with the development of a local stock exchange.